Perbedaan Kinerja Baznas dan Lazismu Berdasarkan Analisis SWOT - Muchammad Adam Chusen; Lalu Khaeril Anwar; Rian Alfi; Arief Safari; Amie Amelia; Nella Sriyama; Maulana Wira Pradhana Maulana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study evaluates the performance of zakat management by the National Zakat Agency (BAZNAS) and the Muhammadiyah Zakat Institution (LAZISMU) using the SWOT analysis method. The findings reveal that BAZNAS has strengths in government legitimacy, resource access, and nationwide coverage, but faces challenges due to complex bureaucracy. In contrast, LAZISMU excels in flexibility and a community-based approach but encounters obstacles such as dependence on donations and income fluctuations. The SWOT analysis identifies the strengths, weaknesses, opportunities, and threats of both institutions, which can be leveraged to formulate more effective zakat management strategies. The study also highlights the importance of data validity and reliability through method triangulation to ensure the findings reflect actual conditions. The qualitative approach provides in-depth insights into the dynamics of zakat management, the challenges, and the opportunities faced. Digital transformation and cross-sector collaboration play a crucial role in optimizing zakat's potential as an economic empowerment instrument. These findings are expected to support the achievement of Sustainable Development Goals (SDGs), particularly in poverty alleviationsv and reducing inequalities.